Adaptability of buildings: a systematic review of current research - Mlote, Doreen Steven; Budig, Michael; Cheah, Lynette (Frontiers in Built Environment, 2024)
The construction industry and associated processes emit about 40%–50% of greenhouse gasses globally, making buildings’ lifelong impact on the environment inevitable. Although research and development stakeholders have directed their focus on various sustainable, recycled, and upcycled building materials, as well as circular designs and construction methods to reduce the adverse effects of environmental challenges, researchers have not yet fully addressed a building’s post-use treatment. Considering that the gap still remains in knowledge concerning how to fully achieve net-zero waste and emissions from construction materials, designs, and processes at the end of a building’s life, this study contributes a concise definition of the concept of adaptability with a holistic review to understand Design for Adaptability (DfA) and its potential to reduce the need for unnecessary new construction and eliminate potential waste. This review used the PRISMA guidelines approach to gather key insights from various articles on the concept of adaptability that are relevant to the scope of buildings. Moreover, this review identifies potential areas of further research that could boost confidence in the use of adaptable strategies in the future. A total of 50 articles out of 170 articles were chosen through a selection process involving a new set of inclusion and exclusion criteria based on PRISMA guidelines. The findings show that demographical, technological, and economic motivations drive adaptability’s functional, environmental, economic, and social benefits. However, the regulatory, technical, economic, and social barriers hinder its implementation in construction processes. The findings also demonstrate that various promising frameworks for assessing adaptability still lack comprehensive guidelines, assessment, and validation methods for the overall implementation of adaptable strategies. Existing frameworks are mostly limited to spatial assessment of the reuse of spaces and do not account for the structural flexibility and performance of load-bearing building elements despite the fact that most assessed papers were from the engineering field. Nevertheless, this paper concludes that adaptability strategies can be implemented early during the construction of new buildings or during the repurposing of existing buildings, with the end goal being to increase the longevity of the use of structures, prevent premature demolition, and minimize unnecessary construction waste.